If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -1p = 15 Solving -2 + -1p = 15 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1p = 15 + 2 Combine like terms: -2 + 2 = 0 0 + -1p = 15 + 2 -1p = 15 + 2 Combine like terms: 15 + 2 = 17 -1p = 17 Divide each side by '-1'. p = -17 Simplifying p = -17
| -6(3h+9)=-22 | | Y/4-7=-3 | | X-3/2=4/8 | | 3(4n+7)=-32 | | 20-n=37 | | 4x1/2=8 | | 60b^2+31b-3=0 | | x^2-34x-273=0 | | 4.75x+2y=3.45 | | -10-a=-15 | | (3+i)(-4+3i)= | | -10-a=15 | | 5a-6-2a=1/ | | P/3-7=14 | | x^2-32x-273=0 | | -k/4-3=10 | | 4a=3.2 | | 6x+4(-3+1x)=13 | | -12=-4/5x | | 6a=6.6 | | 5p+6=4-8 | | 2y=2.2 | | -8+12=2x+11 | | y^2-34y-273=0 | | 2x^3-10x-1=0 | | X+28+(6x+5)+39=180 | | 17x^3-10x-1=0 | | G*2=30-7g | | 5w-7(0.5w+8)=-7(3+w) | | y=15x-9 | | 5/8j=-1 | | 5p(3-5)=-4(6-p) |